A Study on the Role of Asraya-Asrayee Bhava Sambandha in the Genesis of Sandhivata w.s.r Shleshaka Kapha - Kour, Amardeep; Bharti, Lotika (International Research Journal of Ayurveda & Yoga, 2022)
Asraya –Asrayee bhava sambandha means relation between Asraya (seat) and Asrayee (seated). In my survey study Asthi Sandhi is the Asraya i.e. seat and Vata and Kapha are Asrayee i.e. seated. Sandhivata occurs when Shleshaka Kapha decreases and Vata increases and hence gets seated in Sandhi. In my survey study I have found that due to various reasons and due to ageing there is an increase in Vata accompanied by a decrease in Shleshaka Kapha. In the survey conducted on 60 patients 51 were having Rukshta, 27 were having Antardaha, 56 were having Sleshmashayashuna, 57 were having Sandhishaithilya, 10 were having Bhrama, 14 were having Hridadrava and 36 were having Daurbalya. This shows there was Kapha Kshaya in all the patients of Sandhivata. Vakparushya is seen in 18 patients., Karshya is seen in 19 patients, Karshnya is seen in 12 patients, Gatrasphurana is seen in 34 patients, Ushnakamita is seen in 40 patients., Nidranasha is seen in 19 patients, Alpabala is seen in 40 patients, Gadavarcha is seen in 15 patients, Anaha is seen in 12 patients, Indriyabhramsha is seen in 14 patients, Pralapa is seen in 5 patients, Dinata is seen in 8 patients and Bhrama is seen in 15 patients. This shows that there is Vata dosha prakopa in Sandhivata. Sandhivata occurs when Vata vitiates and gets seated in Sandhi where Shleshaka Kapha is also present. And vitiated Vata will cause decrease of Shleshaka Kapha. Because both the Dosha‟s is having opposite Gunas. And Vridhi of one Dosha will leads to Kshaya of another Dosha resulting in the diseased state called Sandhivata). In this research article describe the role of asraya-asrayee bhava sambandha in the genesis of sandhivata w.s.r shleshaka kapha.